Axon bundle spacing in the anterior cingulate cortex of the human brain. - Di Rosa, E; Crow, T; Chance, SA (2008)
The anterior cingulate cortex (ACC) is implicated in neuropsychiatric disorders. Post-mortem axon bundle data will be important to complement novel MRI methods for analysing cortical diffusion data. [Jespersen SN, Kroenke CD, Ostergaard L, et al. Modeling dendrite density from magnetic resonance diffusion measurements. Neuroimage. 2007;34:1473-86] Therefore we aimed to assess perimeter, area, density and spacing of axon bundles in BA24 not previously measured in the human ACC using image analysis of 10 microm-thick tangential sections of layer IV in 4 normal patients. Axon bundle mean perimeter was 53.8 microm, mean area was 197.1 microm(2), mean density was 226.3/mm(2), and mean spacing was 73.8 microm. Thus, axon bundles were widely spaced relative to cell body minicolumns and other prelimbic areas. A review of the literature suggests that there is hierarchical regional variation of bundle and column spacing.